Pharmaceutical Targeting of the Brain - Krizbai, István A.; Nyúl-Tóth, æ#129;dám; Bauer, Hans-Christian; Farkas, Attila E.; Traweger, Andreas; Haskó, János; Bauer, Hannelore; Wilhelm, Imola (Current Pharmaceutical Design, 2016)
Besides being indispensable for the protection and nutrition of the central nervous system (CNS), blood-brain barrier (BBB)-forming cerebral endothelial cells (CECs) have a major role in hampering drugs to reach therapeutically relevant concentrations in the brain. In this respect, the most important defense systems of CECs are tight junctions (TJs) sealing the paracellular way of transport, efflux pumps (ABC transporters) and metabolic enzymes. Here we review current strategies aiming at overcoming the BBB with the purpose of effectively delivering drugs to the CNS. Besides chemical modification of drug candidates to improve CNS availability, the main strategies include: bypassing the BBB (intracranial or nasal routes), reversible opening of TJs (using hyperosmotic mannitol, ultrasounds, peptides and other physical methods or chemical agents), vector-mediated drug delivery systems (nanocarriers, exploitation of receptor- and carrier-mediated transport) and inhibition of efflux transporters. We discuss the main advantages, disadvantages and clinical relevance of each strategy. Special emphasis will be given to the description of the chemical characteristics of nanoparticles (lipidic, polymeric, inorganic, etc.) and the main strategies of targeting them to the CNS.
Keywords: ABC transporter